Parental Behavior: Effects of Infants’ Age and Type of Interaction - Guerrero, Bárbara; Alva, Elda Alicia (Revista de Psicología, 2016)
Both the child’s age and the presence or absence of a parental member affect maternal and paternal behavior patterns. However, parents may show differential sensitivity to these factors, so they should be examined together. The purpose of this research was to observe whether there were differences between the paternal and maternal behaviors and if this differences were dependent on the child’s age and the type of interaction. The frequency of 15 parental behaviors, corresponding to 30 couples, was longitudinally registered. Participants were asked to play with their babies, of 15 and 21 months, in three forms: mother-baby (dyadic interaction), father-baby (dyadic interaction) and mother-father-baby (triadic interaction). Results showed that parents presented differential sensitivity according to the age of the baby and the type of interaction, for the differences between paternal and maternal behaviors depended both on the baby’s age and the type of interaction they had. This reflects that family works like a system and that triadic interaction is far more complex than dyadic interaction.